Analysis of Symptomology, Infectiveness, and Reinfections between Male and Female COVID-19 Patients: Evidence from Japanese Registry Data - Meng-Hao Li (MDPI AG, 2021)
Background: Hokkaido was the first Japanese prefecture to be affected by COVID-19. Since the beginning of the pandemic, the Japanese government has been publishing the information of each individual who was tested positive for the virus. Method: The current study analyzed the 1269 SARS-CoV-2 cases confirmed in Hokkaido in order to examine sex-based differences in symptomology and infectiveness, as well as the status of reinfections and the viral transmission networks. Results: The majority of asymptomatic patients were females and older. Females were 1.3-fold more likely to be asymptomatic (p < 0.001) while a decade of difference in age increased the likelihood of being asymptomatic by 1% (p < 0.001). The data contained information up to quaternary viral transmission. The transmission network revealed that, although asymptomatic patients are more likely to transmit the virus, the individuals infected by asymptomatic cases are likely to be asymptomatic (p < 0.001). Four distinct co-occurrences of symptoms were observed, including (i) fever/fatigue, (ii) pharyngitis/rhinitis, (iii) ageusia/anosmia, and (iv) nausea/vomiting/diarrhea. The presences of diarrhea (p = 0.05) as well as nausea/vomiting (p < 0.001) were predictive of developing dyspnea, i.e., severe disease. About 1% of the patients experienced reinfection. Conclusions: Sex and symptomatology appear to play important roles in determining the levels of viral transmission as well as disease severity.